Thermophysical Properties of Porous Media: Consolidated Sandstones (Biological Sciences - PJSIR, 2006)
Thermal conductivity and thermal diffusivity of porous rocks have been measured simultaneously by Gustafsson probe in the temperature range of 280-330 K at normal pressure using air as the saturant. Data are presented for five types of samples ranging in porosity from 8 to 17%, and to show the variation of thermal conductivity with porosity. An empirical formula is suggested to account for the estimation of thermal conductivity of porous sandstones in terms of porosity and thermal conductivities of the mineral constituents. Thermal conductivities of the samples do not change much within the temperature of measurement.